Food and nutritional security of families assisted by the Bolsa Família cash transfer program in primary health care - Müller Pacheco, Pauline; de Oliveira Pedroso, Márcia Regina; Carvalho Gonçalves, Samira; Macedo Cuervo, Maria Rita; Rossoni, Eloá (O Mundo da Saúde, 2018)
The Bolsa Família cash transfer program advocates access to health and monitoring the nutritional status of the families attended. Considering this, this study sought to estimate the nutritional status of children under five years and the Food Security level of families assisted by the cash transfer program, Bolsa Família (PBF), in three Family Health Units (FHU) in Porto Alegre, RS, Brazil and its association with socioeconomic variables. A cross-sectional study was carried out in 2012 with 101 families registered in the PBF with children under five years from three FHUs. Data collection was taken by a socioeconomic questionnaire, anthropometric assessment and application of the Brazilian Food Insecurity Scale (EBIA). Were performed descriptive analyses and chi-square tests. Food insecurity frequency was 89.1%; 4.5% and 9.1% of children had short stature and overweight/obesity, respectively. The food insecurity was associated with low maternal education. A high frequency of food insecurity was found; thus, this study has contributed to stimulating food and nutrition surveillance of this population in the FHUs studied.